Inggris - Nurhayati, Fitriani; Fathimah, Nur Sab’rina; Abdillah, Naufal; Nurdiansyah, Achmad; Maulana, Hamdan; Santora, Pipih; Faiz, Karman; Desi, Rosulina; Koswara, Ujang (Institut Agama Islam Negeri Kendari, 2025)
This study examines the implementation of technology-based evaluation at a junior high school at Nagreg, Indonesia, focusing on teacher and student experiences. Using a qualitative narrative approach, data were gathered through in-depth interviews with five PAI teachers and twenty students, classroom observations, and document analysis, and analyzed using Spradley’s componential analysis. The findings indicate that teachers view digital platforms such as Google Forms and Quizizz not simply as alternative tools, but as mechanisms that reduce administrative workload and create space for pedagogical reflection. Students reported lower assessment anxiety and higher engagement, particularly through gamified evaluation formats. Technology also functioned as a creative medium to reinforce Islamic values through multimodal feedback. Despite these benefits, limitations related to infrastructure and unequal digital access persist.